Aging of zinc added to soils with a wide range of different properties: Factors and modeling. (9th August 2017) - Zhang, Xi; Jiang, Bao; Ma, Yibing
Abstract: The aging of metals added to soil is significant in ecological risk assessment and the derivation of soil environmental quality criteria. Semimechanistic aging models have been developed for some metals, but not for zinc (Zn). In the present study, a published dataset detailing the changes in isotopic exchangeability with time, after water‐soluble Zn was added to 23 soils and incubated for 813 d, was used to analyze the effect of soil properties on aging and develop empirical and mechanistic models. Aging was mainly controlled by soil pH, probably because of precipitation, and was linearly correlated with the square root of incubation time, probably as a result of diffusion. Based on precipitation, diffusion, and/or occlusion, semimechanistic aging models were developed using a Zn hydrolysis constant of 6.52 to 6.61, apparent diffusion rate coefficient ( D/r 2 ) of 1.41 × 10 −5 /d, and a root mean square error of less than 15%. The optimized models were accurately validated by 4 independent field‐incubated soils, with different doses of Zn under different conditions (the differences between measured and predicted isotopically exchangeable Zn were less than 10%). This enabled an understanding of the long‐term behavior of Zn added to soils, and the results can be used for environmental risk assessments and the normalization of ecotoxicity datasets in the derivation of soil environmental quality criteria. Environ Toxicol Chem 2017;36:2925–2933. © 2017 SETAC